Nir. read It. write It. draw It: The neat pig - Gaydos, Nora (Norwalk : Innovative Kids, 2008)
This extension of the award-winning, best-selling series by acclaimed author Nora Gaydos, engages kids in an entertaining, hands-on reading, writing, and drawing experience! Reading and writing naturally go hand-in-hand, but the Read it - Write it - Draw it series goes a step further! The third component, drawing, lets kids exercise their imaginations as they add their own creative touch to the story. Pig wants to be clean, but will his mom and dad ever understand?
A
b
b
Keywords: Children's Fantasy -- Young Readers -- Reader Pigs